Navigating Hyperreality: Transmedia Storytelling and Virtual Influencers in Digital Public Relations - Christin, Maylanny; Baskoro, M. Lahandi; Hidayat, Dasrun (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
In a digital era, full of challenges, the phenomenon of hyperreality was becoming increasingly prominent, narrowing the difference between the real physical world and the world of digital simulations. Thanks to advances in technology, virtual influencers appear on social media as virtual figures who behave like real humans. This research seeks to discuss the impact and potential of virtual strategies in public relations (PR) practice in the digital realm. Integrating the concept of transmedia storytelling, the implication of this approach from a communication science perspective is to create a narrative flow that strengthens communication and messages. Characters and figures are created in such a way that they involve three elements, namely the storyteller, the fairy tale and the interacting listener. The storyteller in this case is the creator of the character, the fairy tale is the scenario in the form of the message to be conveyed, the listener who interacts is the involvement that is created. The aim of this research is to determine Hyperrealism in Transmedia Storytelling in Digital Public Relations Activities. This study uses a case study method with a common case approach, which takes Miquela as a virtual influencer case for further study. The research results highlight changes in communication activities from conventional to modern, especially through the use of technology and social media. Furthermore, this research shows that, in facing the complex digital era, PR needs to build and maintain a reputation that is honest, transparent and balanced between the digital and real worlds. In essence, this research not only provides theoretical input but also provides practical insight for PR professionals to face the dynamics of communication in the ever-growing digital world.